Distribution center logistics optimization model - City of Rijeka case study - Jardas, Mladen, inženjer pomorstva (Array, 2020)
The optimization of the goods delivery to Rijeka’s city center presents a complex organizational framework where many parameters must be taken into account and a diverse multi-methodological approach, needs to be utilized. The building of a distribution center is asserted here to be one notable way to improve the existing delivery service. The grouping of freight in a distribution center would result in a reduction of transport costs due to a smaller number of vehicles entering the city center, in turn reducing the traffic burden incumbent on the city’s transport network. In this paper, two of the many possible methods related to the optimization of goods delivery in city centers, have been used. Based on the data collected through the study’s questionnaire, conducted in the area of the city of Rijeka, the method of gravity center has been used to determine the location of the distribution center. Then, based on the tentative location of the distribution center, the method of optimization of the transport process has been applied by resorting to transport problem-solving methods, including several different implementation scenarios. From the proposed solutions, and based on the results detailed, the solution that was found to be the most credible was arguably the best match with the default criterion.